Clinical study, management and outcome of gall bladder perforation in a tertiary care hospital - Balsarkar, Dharmesh J.; Chauhan, Surajsinh A. (International Surgery Journal, 2020)
Background: The objective of the study was to present our clinical experience with gall bladder perforation cases. This may help in the management and decision making of such cases. Methods: Records of 480 patients who received medical and/or surgical treatment with the diagnosis of acute cholecystitis in our hospital between 2007 and 2014 were reviewed retrospectively. Twenty nine (6%) of those patients had gall bladder perforation. Original Niemeier’s classification of gall bladder perforation used to describe the type of perforation. The parameters including age, gender, duration of symptoms, diagnostic procedures, medical or surgical or radiological interventional treatment used, morbidity and mortality were evaluated. Results: Out of the 29 patients, 25 patients had subacute type of gall bladder perforation (Niemeier type II) and 4 patients had chronic (Niemeier type III) perforation. None of the patients encountered had generalized peritonitis (Niemeier type I). The diagnosis in all these patients was established on admission to the hospital by means of abdominal ultrasound and computed tomography. Twelve (43%) patients underwent early surgery. The rest (58.6%) either underwent conservative medical line of management or pigtail catheter insertion in the collection followed by interval cholecystectomy. Three (10.7%) patients died of sepsis and associated comorbid condition. Conclusions: Early diagnosis of gall bladder perforation is of critical importance. Abdominal ultrasound coupled with computerized tomography is useful in diagnosis of gall bladder perforation. Management strategies include early surgery in patients with generalized peritonitis or suspicion of gall bladder necrosis, and initial conservative line of management and/or pigtail insertion in surgically high risk patients which can be followed up by interval cholecystectomy.